A Foucauldian reading of the multiple mini-interview tool used in Canadian physiotherapy admissions. - Otubusen, Oyindamola; Thille, Patricia (Physiotherapy Theory & Practice, 2026)
Physiotherapy education in Canada, like many professional training programs, relies on categorization tools to determine who is most suitable for entry. One such tool is the Multiple Mini-Interview (MMI), an examination which is widely accepted as a fair, objective, and evidence-based method for assessing non-academic competencies. In this professional theoretical paper, we interrogate assumptions supporting its use through a Foucauldian reading of the MMI, examining it as an instantiation of disciplinary power. Rather than assessing whether the MMI "works" in predictive terms, we focus on the form of power underpinning yet concealed within it. By reading the MMI through a Foucauldian lens, we unsettle its taken-for-granted neutrality and call attention to the institutional logics that shape who gains access to the Canadian physiotherapy academy. We argue that, consistent with Foucault's theorization, the MMI encourages applicants to internalize and perform institutionally sanctioned norms of the "ideal" candidate, shaping admissions in ways that favor those with particular cultural and communicative skills who can anticipate and align with these expectations. These candidates are more likely to be perceived as "trainable" and therefore admissible. Thus, while framed as an equitable assessment, the MMI may reinforce Eurocentric and White institutional normativity, a recognized problem within Canadian physiotherapy programs. In this way, the MMI risks contributing to the profession's demographic homogeneity and perpetuating structural disadvantage for some applicants.